The effect of score components on total score in the individual apparatus qualification of 1st Rhythmic Gymnastics Junior World Championships - Tatlibal, P.; Kutlay, E.; Oral, O. (Science of Gymnastics Journal, 2022)
The study aims to determine the effect of the total score components on the total score and the differences between the score components in the 1st Rhythmic Gymnastics Junior World Championship individual apparatus qualification held in Moscow, Russian Federation, in2019. In this study, 1708 scores of 138 gymnasts from 61 countries were analyzed in all routines. For all routines, the effects of difficulty subgroup scores (D1-2, D3-4) on difficulty total scores (DTS), execution subgroup deduction scores (E1-2, E3-4-5-6) on execution total scores (ETS), and the effects of DTS and ETS on total scores (TS) were examined. Descriptive statistics, linear regression, and one-way ANOVA analysis were used. In linear regression analysis results, it was observed that the effect of DTS on TS was higher than the effect of ETS on TS in rope, ball, clubs, and ribbon routines. Among all apparatus, the effects of DTS and ETS on TS were observed as the highest in the clubs routines and the lowest in the rope routines. The effect of D3-4 on TS was higher than D1-2. The effect of deduction E3-4-5-6 on TS was higher than E1-2 (p<0.001). Statistically significant differences were found only between the DTS mean scores of the apparatus (p<0.000) analyzed with one-way ANOVA. This has led to a conclusion that the balance in the effect of TS components on TS scores will contribute to the integrity and the artistic impact of routines and also lead to better results, therefore more time should be devoted to rope and ribbon routines in the early stages of physical preparation.